Level of CD 20-expression and efficacy of Rituximab treatment in patients with resistant or relapsing B-cell prolymphocytic leukemia and B-cell chronic lymphocytic leukemia - Dengler, Jolanta; Topaly, Julian; Frühauf, Stefan; Hensel, Manfred; Ho, Anthony Dick (Leukemia and lymphoma, 2002)
Rituximab (IDEC C2B8) is a chimeric human-mouse monoclonal anti-CD20 antibody that has been proven to be effective for the treatment of patients with CD20 positive leukemia and lymphoma. The level of CD20-expression in patients with B-cell chronic lymphocytic leukemia (B-CLL) is low in comparison to other B-cell lymphomas and normal B-cells. Previous experience with rituximab treatment in small series of patients with B-CLL suggest that it is less effective in B-CLL than in follicular lymphomas. We analyzed the correlation between CD20-expression level and efficacy of rituximab treatment in eight patients with refractory or relapsed B-CLL and two patients with B-cell prolymphocytic leukemia (B-PLL). We could not identify any correlation between CD20-expression and efficacy of rituximab treatment.